1966
DOI: 10.1080/00288233.1966.10420786
|View full text |Cite
|
Sign up to set email alerts
|

Leaching losses of sulphate from superphosphate and gypsum applied on a soil from rhyolitic pumice

Abstract: In studies on Waipahihi sand, a yellow-brown pumice soil of the Taupo suite, 97% or more of sulphate applied as superphosphate or gypsum was leached out under an alternate leaching and drying procedure.Losses were proportional to the amounts applied. They were unaffected by particle size of gypsum over the ranges [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and 60-120 mesh (B.S.S.), except in the first leaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
1983
1983

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Laboratory and glasshouse studies have shown that many overseas and New Zealand soils have a high potential to lose S via subsurface drainage or leaching (Hogg & Cooper 1964;Hogg 1965;Cooper & Hogg 1966;Muller & McSweeney 1974;Peverill & Douglas 1976). This potential is affected by soil characteristics and fertiliser form (Chao et al 1962;Muller & McSweeney 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory and glasshouse studies have shown that many overseas and New Zealand soils have a high potential to lose S via subsurface drainage or leaching (Hogg & Cooper 1964;Hogg 1965;Cooper & Hogg 1966;Muller & McSweeney 1974;Peverill & Douglas 1976). This potential is affected by soil characteristics and fertiliser form (Chao et al 1962;Muller & McSweeney 1974).…”
Section: Introductionmentioning
confidence: 99%